Fabrication of omega-3 fatty acid nanoencapsulation with a sodium alginate-acacia gum complex: In vitro digestibility and biocompatible therapeutic potential - Naorem Rojita Devi; Sital Khandelwal; Srinivasan Pappu (Kuwait Journal of Science)
Omega-3 fatty acids (ω3FAs) possess various health benefits but face challenges due to limited solubility and susceptibility to oxidation. In this study, a sodium alginate-acacia gum (SA-AG) complex was developed to address these issues. The stability of the complex was confirmed through zeta potential and thermogravimetric analysis. ω3FAs were encapsulated within the SA-AG complex, and their physical, morphological, and chemical characteristics were evaluated. Simulated in vitro digestion was used to assess the bio-accessibility of the encapsulated ω3FAs (Enω3FAs), and antioxidant, antibacterial, and toxicity tests were conducted. The SA-AG complex exhibited a zeta potential of −40.3 ± 9.48 mV and remained stable up to 240 °C. The oxidative stability of the complex was maintained for up to 90 days post-formulation. The average particle size was 961.9 nm, with spherical structures observed. Energy Dispersive X-ray Analysis (EDAX) showed the presence of ω3FAs at specific peaks (0.05, 0.5, and 1–1.2 KeV), while Fourier Transform Infrared (FT-IR) analysis confirmed the functional groups of ω3FAs at specific bands (3301 cm−1 and 1630 cm−1). Enω3FAs exhibited rapid release of ω3FAs under gastrointestinal conditions, starting at 45 min with 40 % lipolysis. The highest antioxidant activities of ω3FAs were observed at a concentration of 2 mg/ml through DPPH (35 ± 3.8 %), ferric reducing antioxidant power (48.85 ± 0.002 %) at 5.12 mg/mL, 20.71 ± 0.95 nmol of nitric oxide at 5.12 mg/mL, and 0.204 ± 0.001 absorbance for lipid peroxidation at 5.12 mg/mL. The minimum inhibitory concentration of Enω3FAs was 64 mg/ml against E. coli, S. pneumoniae, and P. aeruginosa, and 16 mg/mL against S. aureus. Enω3FAs also demonstrated the ability to reduce biofilm formation by approximately 50 % and induce a 30 % reduction in existing biofilms at a concentration of 4 mg/ml. Additionally, Enω3FAs were found to be biocompatible, with 0 % mortality observed after 24 h of treatment on Artemia franciscana nauplii. In conclusion, Enω3FAs show therapeutic potential within a stable formulation using the SA-AG complex, providing a promising approach for drug and food delivery systems.